Una evaluación de la competencia en el sector bancario de Argentina: Evidencia empírica con datos a nivel de banco - Héctor Gustavo González Padilla (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2010)
– The profit-maximizing and oligopoly bank model developed by Bresnahan and Lau allows determining the degree of market power held by an average bank. The equilibrium price equation includes a mark up, which is not used in the case of perfect competition but which is partially used in the case of oligopoly or monopolistic competition, and it is fully used in the case of monopoly. This paper explores the degree of competition in the credit market of Argentina in the period 2002-2007. The hypothesis of perfect competition in the loan market can be rejected.
Keywords: E43; E51; F36; G21; L1; 330; Argentina; banks; Cournot equilibrium; market power; loan markets; oligopoly; perfect competition; Bank; Kreditmarkt; Marktstruktur; Argentinien